The Chemical Composition of Egyptian Moringa Oleifera Grown in Different Agro-Ecological Regions (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Moringa Oleifera plant is successfully grown in Egypt now their leaves are highly nutritious and can be eaten either fresh or cooked. Aim Evaluate chemical composition of Egyptian Moringa Oleifera leaves grown in different agro-ecological regions. Methods; Same age leaves were collected from private farm in Gharbiya governorate (loam soil) and from western dessert (sandy soil). Leaves were subjected to proximate, vitamin, minerals and antioxidants analysis. Results; soil types widely affect the results depending on the nutrients and ph value. Fresh leaves contain the highest moisture content and the lowest nutrients comparing to dried leaves. Moringa Oleifera grown in sandy soil had the highest content of ash, carbohydrate and minerals including; Ca, Zn, Na, K, Mg and Fe compared to which grown in loam soil. Vitamin C, beta carotene, total phenolic, total flavonoids, and total antioxidant capacity were higher in leaves cultivated from loam soil than sandy soil as  67.93, 1497, 58.9, 90.8 mg/g , 65% and 60.5, 1303.9, 50.4, 80.5mg/g, and 59% respectively. Variability in chemical composition is likely due to differences in soil, climate, and plant age. These relatively diverse chemical constituents may be responsible for the medicinal properties of Moringa Oleifera leaves